The Diffusion of Innovations Model: Applications to Education Policymaking and Critique - Marzul Hidayat; Amirul Mukminin (Edukasi, 2022)
The origins of the diffusion of innovations theory are varied and span across various disciplines, and in a sort of contexts. The diffusion of Innovation framework is a theory of how, why, and at what rate new ideas, concepts, technology, technical information, and actual practices spread or diffuse through cultures or system. When innovations happen, innovations may be spread from the innovator (a state or government) to any other groups (states or governments). The inquiries of state policy innovation have been a foremost subject in political science and public policy. Political and policy academics and scholars are attracted in looking at how and why a policy or program spreads (diffusion) from one state government to another and what make happen a government or state to adopt a new program or policy. This paper will focus on (1) the diffusion of innovations model’s general characteristics, its theoretical origins and application across fields, (2) the history of its application to policy and politics and the central premise, (3) the dominant methodological tradition in policy and political science, (4) applications to education policymaking, and (5) the limitation.